EFL students’ social identities construction through gender-based short stories - Benavides Buitrago, Catherine (Colombian Applied Linguistics Journal, 2017)
This article reports an action research study that took place in a public school in Bogota with 38 students from 7th grade who were between 12 and 16 years of age. The study intended a) to identify discourses students draw on to construct social identities in the EFL classroom while reading short stories about gender topics b) to describe social identities constructed discursively in relation to gender-based short stories and c) to study the potential relationship between these discursively constructed social identities in gendered-related reading activities and foreign language learning. This post-structuralist study focused on the topics of gender, social identities, and students’ discourses, definitions that were defined and described in its theoretical framework. Data were collected by observing and analyzing three pedagogical units based on short stories about equality, multiplicity, and respect and designed by following the stages of the Task Based Learning Approach (TBL). Field notes, video and audio recordings, and students’ artifacts were analyzed by following the steps proposed by grounded theory (GT; Charmaz, 2006) and the principles of critical classroom discourse analysis (CCDA; Kumaravadivelu, 1999). Data analysis revealed a main category and three subcategories which showed the relationship between the gender-based short stories read by the students and the discourses they created during the lessons.